Central Bank Governor Turnover And Inflation In Zambia:Using Complex Wavelets for a Clearer Picture - Andrew Phiri (Cogent Business & Management, 2022)
The Bank of Zambia has one of the highest central bank turnover averages in Africa and the inflationary effects of the low central bank autonomy are yet to be empirically quantified. This study develops an index of central bank turnover for the Zambian economy extending from 1984 to 2020 and applies continuous wavelet coherence techniques to examine its co-movement with inflation in a time-frequency domain. We find negative co-movements between the variables across the entire time window with higher (lower) frequency correlations being dominant in the pre-2000 (post-2000) period. Moreover, the phase difference dynamics indicate that central bank turnover has led inflation in all periods except during the 1990-1995 and 2016-2020 periods where reverse causality is observed. Altogether, our study paints a detailed narrative on the relationship between the variables for the Zambian economy and offers policy advice aimed at strengthening the independence and credibility of the country's central bank.
Keywords: 650; inflation; Central bank governor turnover; complex Morlet wavelets; wavelet coherence; wavelet power spectrum